2016
DOI: 10.1007/s13187-016-1076-4
|View full text |Cite
|
Sign up to set email alerts
|

Developing Sustainable Cancer Education Programs: Training Public Health Students to Deliver Cancer 101 in Puerto Rico

Abstract: The use of promotores to educate Hispanic communities about different health topics has been proven successful, albeit with limitations in program sustainability. The goal of this study was to develop a sustainable train-the-trainer model to train graduate public health (PH) students to disseminate cancer education among communities in Puerto Rico (PR). Graduate students (n = 32) from Ponce Health Sciences University's (PHSU) PH program participated in a 2-day Cáncer 101 training, where they learned how to del… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 14 publications
0
2
0
2
Order By: Relevance
“…When mentioned, researchers most frequently noted social cognitive theory (Alvarez‐Hernandez et al, 2021 ; Fleming et al, 2018 ; Hoeft et al, 2015 ; Rivera et al, 2018 ; Taverno Ross et al, 2021 ) and Freirean pedagogy (Bonilla et al, 2012 ; Kutcher et al, 2015 ; Moore‐Monroy et al, 2013 ; Sánchez et al, 2012 ). Cupertino et al ( 2013 ) used both social cognitive theory and Freirean pedagogy in their CHW training framework to situate the CHW program within the larger community social network and implement the training with participatory and interactive pedagogical tools such as open discussions and roleplaying.…”
Section: Resultsmentioning
confidence: 99%
“…When mentioned, researchers most frequently noted social cognitive theory (Alvarez‐Hernandez et al, 2021 ; Fleming et al, 2018 ; Hoeft et al, 2015 ; Rivera et al, 2018 ; Taverno Ross et al, 2021 ) and Freirean pedagogy (Bonilla et al, 2012 ; Kutcher et al, 2015 ; Moore‐Monroy et al, 2013 ; Sánchez et al, 2012 ). Cupertino et al ( 2013 ) used both social cognitive theory and Freirean pedagogy in their CHW training framework to situate the CHW program within the larger community social network and implement the training with participatory and interactive pedagogical tools such as open discussions and roleplaying.…”
Section: Resultsmentioning
confidence: 99%
“…La formación académica y capacitación de forma sostenible a los profesionales de la salud es un factor clave a considerar en la prevención de cáncer (34,35). El presente trabajo encontró que las habilidades académicas y diagnósticas son óptimas en la prevención y detección temprana del cáncer de cuello uterino, esto puede deberse que este cáncer es una de las principales causas de muertes en el Perú, existe difusión por medios de comunicación las medidas preventiva para el cáncer de cuello uterino, así mismo con frecuencia se pueden observar a los pacientes en los centros de salud, pero en estados avanzados del cáncer (20,36,37).…”
Section: Discussionunclassified
“…Prior studies found that internet and social media‐based medical information was frequently incorrect with 12%–40% of health‐related tweets described as untrustworthy or inaccurate (Albalawi et al 2019 ; Gage‐Bouchard et al, 2018 ; Kedzior et al, 2019 ; Love et al, 2013 ; Shah et al, 2019 ). Assuming an inaccuracy rate within this range, it was estimated that a sample size of at least 369 tweets would be needed to derive an overall accuracy with 95% confidence that was within 5% of these values.…”
Section: Methodsmentioning
confidence: 99%